(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: The prison population of any country is a high-risk population because of a lack of access to regular health care facilities. This research was planned to assess the gender differences in the health status of the imprisoned population of Lahore. Patients and methods: An analytical cross-sectional study was conducted in Kot Lakhpat Jail in the province of Punjab, near Lahore, from January to August 2019. After getting permission from Inspector General, Police of Punjab, a sample of 320 inmates of Kot Lakhpat Jail was collected through a simple random sampling technique. Data was collected on a structured questionnaire based on history and examination. Data was entered in SPSS version 23, and the chi-square test was applied to assess the gender differences in health status, p-value ≤ 0.05 was taken as significant. Results: General examination revealed that 143 (44.7%) had refractory errors, and 34 (10.6%) had mild deafness. Common infection in males were scabies (p = 0.002), Sore throat (p =0.015) and urinary tract infections (p=0.015). Hepatitis C was present in high frequency (9.1%). Assessment of sexually transmitted diseases showed discharge in 10.6%, vesicular herpetic eruptions in 8.8%, and ulcers in private parts in 3.8% of the sample. Males showed a significantly high frequency of hypertension (p =0.052) and arthritis (p=0.024). Evaluation of mental health status revealed significant high rates of depression in females (p =0.000) and a high frequency of insomnia (p=0.000). Social health problems revealed a high frequency of smoking in males (p=0.000) and feeling of stigmatization in females (p=0.000). Conclusion: Male jail inmates showed high frequencies of scabies, sore throat and urinary tract infection, and hypertension. Females showed higher rates of depression, insomnia, and feeling of stigmatization.